PENGARUH ENTERPRISE RISK MANAGEMENT TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN LAPORAN KEBERLANJUTAN SEBAGAI VARIABEL MEDIASI - Lana, Anastasia; Oktorina, Megawati (Faculty of Economics and Business, 2024)
The purpose of this research is to analyze the effect of enterprise risk management to firm value mediated by sustainability report. The sample used was 94 set data from consumer non-cyclical companies and health companies listed on Indonesia Stock Exchange in 2018-2021. The variables used were enterprise risk management, sustainability report, and firm vaue. The results showed that enterprise risk management has a positive effect on firm value and on sustainability report. Sustainability report has not affect on firm value. Sustainability report has not mediated the effect of enterprise risk management to firm value. Keywords: Enterprise Risk Management, Sustainability Report, Firm Value, Mediation